RETRACTED: Modeling Cardiac Dysfunction Following Traumatic Hemorrhage Injury: Impact on Myocardial Integrity - Wall, Johanna; Naganathar, Sriveena; Praditsuktavorn, Banjerd; Bugg, Oscar F.; McArthur, Simon; Thiemermann, Christoph; Tremoleda, Jordi L.; Brohi, Karim (Frontiers in Immunology, 2019)
Cardiac dysfunction (CD) importantly contributes to mortality in trauma patients, who survive their initial injuries following successful haemostatic resuscitation. This poor outcome has been correlated with elevated biomarkers of myocardial injury, but the pathophysiology triggering this CD remains unknown. We investigated the pathophysiology of acute CD after trauma using a mouse model of trauma haemorrhage shock (THS)-induced CD with echocardiographic guidance of fluid resuscitation, to assess the THS impact on myocardial integrity and function. Mice were subjected to trauma (soft tissue and bone fracture) and different degrees of haemorrhage severity (pressure controlled ~MABP <35mmHg or <65mmHg) for one hour, to characterise the acute impact on cardiac function. In a second study, mice were subjected to trauma and haemorrhage (MABP<35mmHg) for one hour, then underwent two echocardiographic-guided resuscitations to baseline stroke volume at 60 min and 120 min, and were monitored up to 180 min to study the longer impact of THS following resuscitation. Naïve and sham animals were used as controls. At 60 min post-THS injury, animals showed a lower cardiac output (CO) and stroke volume (SV) and an early rise of heart fatty acid-binding protein (H-FABP=167±38 ng/ml; 90% increase from shams, 3.54±3.06ng/ml), when subjected to severe haemorrhage and injury. Despite resuscitation, these animals maintained lower CO (6 ml/min vs 23ml/min), lower SV (10 μl vs 46 μl; both ~75% decreased), and higher H-FABP (levels (340±115 ng/ml vs 10.3±0.2ng/ml; all THS vs. shams, P<0.001) at 180 min post-TH injury. Histopathological and flow-cytometry analysis of the heart confirmed an influx of circulatory leukocytes, compared to non-injured hearts. Myocardial injury was supported by an increase of troponin I and h-FABP and the widespread ultrastructural disorganisation of the morphology of sarcomeres and mitochondria. DNA fragmentation and chromatin condensation driven by leakage of apoptosis-inducing factor (AIF) may suggest a mitochondria-driven progressive cell death. THS modelling in the mouse results in cardiomyocyte damage and reduced myocardial function, which mimics the cardiac dysfunction seen in trauma patients. This CD model may, therefore, provide further understanding to the mechanisms underlying CD and act as a tool for developing cardioprotective therapeutics to improve survival after injury.